Innovative handcycling training interventions: Optimizing performance - Perret, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Handcycling performance has considerably improved in the last decades and winning or losing a time trial race of about 25min duration is nowadays a question of only few seconds. Whereas the difference between first and third place at the Athens Paralympic Games 2004 (first time that handcycling was a Paralympic discipline) was 4.9%, it dropped below 0.6% in the same race category at the London Paralympic Games 2012. Such examples underline the necessity of optimizing training interventions and equipment for athletes in order to achieve top class performance. Methods: Beside conventional training strategies, the following presentation will focus on various interventions in order to improve handcycling performance based on study results but also on personal single case experiences working with elite handcyclists with a spinal cord injury. Such interventions include respiratory muscle training, nutritional interventions (e.g. supplementation) as well as individual equipment adaptations based on wind tunnel experiments. Results: In general, handcyclists seem to benefit from respiratory muscle endurance training and some supplementation strategies (e.g. caffeine, basic salts) as well as from adaptations of the personal equipment. However, benefits seem to differ from athlete to athlete and vary widely depending on individual factors such as completeness and level of lesion. As a consequence one has to take into account the special physiological constraints of persons with a spinal cord injury concerning e.g. energy expenditure and thermoregulation. Conclusions: There seem to exist several intervention strategies in handcycling to further optimize exercise performance. However, personal circumstances such as level and severity of impairment have to be taken into account and individual solutions have to be found for elite athletes with a spinal cord injury.